Qualitative Analysis of Factors Influencing Compliance with Medication in Pregnant Women and Suffering Families Tuberculosis: Application of Theory Health Belief Model - Ratnasari, Dewi; Sahrudi, Sahrudi (Indonesian Journal of Global Health Research, 2024)
Tuberculosis (TB) has contributed 25% of the total number of deaths. It is estimated that 98% of deaths due to TB occur in developing countries. So the success of treating TB really depends on the patient's compliance with taking medication, especially in groups at risk of contracting TB such as pregnant women. Compliance is greatly influenced by various factors and is very dependent on behavior. One of the most popular theories in explaining behavior is the health belief model. The aimed of this research is to explore the factors influencing compliance with medication in pregnant women with tuberculosis using theory of health belief model. This research is a qualitative analysis using a health belief model approach. This research will be conducted in the work area of the Cimarga Community Health Center in December 2023. Data collection was carried out using in-depth interviews with researchers using the triangulation method. There were 4 main informants, 2 triangulators, and 4 supporting informants. The approach used is perception of vulnerability, severity and perception of benefits The result of this research are: (1) perceived susceptibility shows that the majority of respondents who adhere to taking medication are aware that this disease is serious and after they are infected, this makes them afraid that people around them such as parents and fetuses will also be infected. (2) Perceived benefits can be measured in the context of TB treatment behavior in pregnant women by asking about improvements in symptoms and perceived changes in physical condition during the treatment process. (3) The perception of severity begins to be felt when the disease begins to cause symptoms and family members become infected quickly. Moreover, those infected are mothers who are pregnant.